Transmission risk of Borrelia burgdorferi sensu lato from Ixodes ricinus ticks to humans in southwest Germany. - Maiwald, M. (Cambridge University Press, 1998)
The risk of Borrelia burgdorferi infection and the value of antibiotic prophylaxis after tick bite are controversial. In this study, performed in two areas of southwestern Germany, ticks were collected from 730 patients and examined by the polymerase chain reaction (PCR) for B. burgdorferi. To assess whether transmission of B. burgdorferi occurred, the patients were clinically and serologically examined after tick removal and during follow-up examinations. Data from all tick bites gave a total transmission rate of 2.6% (19 patients). Eighty-four ticks (11.3%) were PCR positive. Transmission occurred to 16 (26.7%) of 60 patients who were initially seronegative and could be followed up after the bite of an infected tick. These results indicate that the transmission rate from infected ticks in Europe is higher than previously assumed. Examination of ticks and antibiotic prophylaxis in the case of positivity appears to be indicated.